Planning model for rural distribution networks with integrated energy stations via robust optimization method - Yang, Zhichun; Min, Huaidong; Yang, Fan; Liu, Yu; Shen, Yu; Zhou, Bin; Zhou, Zhiqiang; Hu, Wei; Lei, Yang (Frontiers in Energy Research, 2024)
With the modernization and intelligent development of agriculture, the energy demand in rural areas continues to increase, which leads to an increased operational burden on the existing rural distribution network. Integrated energy stations (IESs), in rural areas, use renewable energy sources such as biogas, wind power, and photovoltaic as energy inputs, which can fully improve energy efficiency and help reduce the operating load and peak valley difference of rural distribution networks. In this paper, a multistage planning model is proposed for rural distribution networks with IESs based on the robust optimization method. Firstly, a rural distribution network operation framework with IESs is proposed, and a mathematical model of rural IESs is built based on the energy hub (EH). Then, the multistage robust planning model of rural distribution net-works with IESs is developed and typical scenarios of stochastic source and load are generated based on improved k-means. An iterative solution method for a two-stage robust optimization method is proposed based on the nested column constraint generation (NC&CG) algorithm. Finally, the effectiveness of the proposed method to relieve the power grid pressure in rural areas is verified through case studies on a modified IEEE 33-node distribution network and a real 152-node distribution network.